Development of Mobile Learning for Simulation and Digital Communications - Amir, Hazira Fakhrurrozi; Huda, Asrul; Maksum, Hasan (Journal of Education Technology, 2020)
Simulation and digital communication subjects at SMKN 1 Singkarak do not have support other than text books and modules. This study aimed to develop a practical and effective learning platform that can support students in learning. This study used a 4D development model, and the trial subjects in this study were 31 students of class X in the 2020/2021 academic year. The instruments used were test and questionnaire instruments. The research method used was pre-experimental. The data obtained were analyzed using quantitative descriptive statistical analysis methods. From the research results, it was found that classical completeness reached 90% and the average score in terms of the gain score of students before and after using mobile learning was 0.49. The conclusion of this research is that the results of assessments from both teachers and students show that mobile learning in simulation and digital communication subjects can be categorized as very practical and effective